Adsorption behavior of gardenia yellow pigment on embedded spherical cellulose adsorbent. Issue 8 (22nd January 2021) - Liu, Jianting; Yu, Zhendong; Li, Qiqi; Lv, Yuancai; Lin, Chunxiang; Huang, Jianhui; Liu, Yifan; Liu, Minghua
Abstract : A spherical cellulose adsorbent embedded with black wattle extract (SABW) was prepared and used to adsorb gardenia yellow pigment (GYP). The result revealed that SABW presented excellent adsorption performance to GYP. Abstract : A spherical cellulose adsorbent embedded with black wattle extract (SABW) was prepared by an inverse suspension method, and used to adsorb the typical food pigment, gardenia yellow pigment (GYP). Results of SEM, XRD, FTIR and BET characterization showed that SABW was composed of abundant porous structures and functional groups such as –CO, –OH and benzene ring groups. The batch adsorption experiments revealed that SABW presented excellent adsorption performance for GYP with a high adsorption percentage of 97.96%. The adsorption process followed the Langmuir and Freundlich adsorption isotherm, and the experimental data were in good agreement with the pseudo-second order dynamic model. Furthermore, the main adsorption mechanism involved hydrogen bonding, electrostatic interaction and pore adsorption. Importantly, the desorption and regeneration experiments showed that SABW had satisfactory reusability and retained 92.30% adsorption after 4 cycles. The above results provide a vital theoretical basis for the extraction of GYP.